2022
DOI: 10.3390/children9111720
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Characteristics of Type 1 Diabetes Children and Adolescents: A Hospital-Based Case-Control Study in Uganda

Abstract: Changes in body composition have been suggested as an intractable effect of Type 1 Diabetes Mellitus and its management. This study aims to compare body composition characteristics in a sample of young children and adolescents with Type 1 Diabetes Mellitus with healthy controls. Methods: In this case–control study, body composition was assessed using bioelectrical impedance among 328 participants. Anthropometric measurements included weight, height, upper arm, hip, and waist, circumferences; biceps; triceps; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nsamba et al observed that children with type 1 DM exhibited a lower PhA than that of age-matched controls (4.94 vs. 5.32, p < 0.001) [28]. Dittmar et al [29] reported that the whole body PhAs of patients with diabetes at 50 and 100 kHz were lower than those of controls; however, the PhA at 5 kHz was higher in patients with diabetes. Furthermore, Kim et al [15] observed that patients with diabetes exhibited a lower PhA at three frequencies (5, 50, and 250 kHz) than that of age-, sex-, and BMI-matched normal controls.…”
Section: Discussionmentioning
confidence: 98%
“…Nsamba et al observed that children with type 1 DM exhibited a lower PhA than that of age-matched controls (4.94 vs. 5.32, p < 0.001) [28]. Dittmar et al [29] reported that the whole body PhAs of patients with diabetes at 50 and 100 kHz were lower than those of controls; however, the PhA at 5 kHz was higher in patients with diabetes. Furthermore, Kim et al [15] observed that patients with diabetes exhibited a lower PhA at three frequencies (5, 50, and 250 kHz) than that of age-, sex-, and BMI-matched normal controls.…”
Section: Discussionmentioning
confidence: 98%
“…Nutrition and obesity in the context of chronic childhood diseases were also present in the topics of the SI. Nsamba et al, who reported higher fat accumulation in Type 1 DM children than in their non-DM counterparts, while abdominal fat accumulation was associated with poorer glycemic control in these patients [2]. Moreover, Ahn et al proposed that the use of Fetuin A-to-Adiponectin ratio could be useful in identifying diabetic obese children and adolescents with a higher probability of developing metabolic complications [3] Two articles from the Greek division of the Global Asthma Network presented important evidence about the protective association between a high consumption of fruits and vegetables with atopic diseases and the important role of socioeconomical status in this relationship [4,5].…”
mentioning
confidence: 93%